Enhanced device lifetime of double-heterojunction nanorod light-emitting diodes. Issue 18 (27th April 2017) - Cho, Seong-Yong; Oh, Nuri; Nam, Sooji; Jiang, Yiran; Shim, Moonsub
Abstract : Origin of device failure in emerging solution-processed, high-performance quantum dot-based LEDs is identified. Abstract : Colloidal quantum dots (QDs) are emerging as solution-processable, high-performance materials for light-emitting diodes (LEDs). Understanding the failure mechanism(s) is of both fundamental and practical importance, yet little is known of how QD-LEDs fail. Here, we have carried out accelerated device lifetime measurements on double heterojunction nanorod- (DHNR) and QD-LEDs. A common dependence of device lifetime on the initial driving voltage is observed over more than two orders of magnitude range in the initial luminance. This behavior is independent of whether the emitting materials are DHNRs or QDs prepared under different conditions. Reducing the hole injection barrier by doping HTL allows lower voltage operation, leading to longer device lifetimes. DHNRs with a band structure that further lowers the hole injection barrier require even lower driving voltages and therefore lead to longer device lifetimes than core/shell QDs. At 1000 cd m −2, the DHNR-LED exhibits no significant degradation even after more than 200 h of continuous operation. QD-LEDs, on the other hand, are completely degraded in less than ∼100 h under the same initial luminance conditions. Hole accumulation/trapping leading to HTL degradation, which in turn deteriorates electroluminescence but not the photoluminescence, is suggested to be the main cause of degradation of both DHNR- and QD-LEDs.